AUDIT MANAJEMEN SEBAGAI PENILAIAN EFEKTIVITAS SUMBER DAYA MANUSIA (Studi kasus pada PT. Shaftindo Energi) - Prastuti, Anindita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Management audit of human resource at PT. Shaftindo Energi aims to know how effective the development of human resource function and identify weaknesses and give recommendation or improvement alternative to reach the effective human resource development. This research used descriptive research method. The datas got from field studies, those are by interview, observation, documentation, and questionnaire. Data analyzing process used a qualitative analysis method by compared three elements which is criteria, cause, and effect to know how succeed the management develop the human resource. The problem boundary is effectiveness assessment of human resource function at PT. Shaftindo Energi. The functions are (1) human resource planning (2) human resource recruitment (3) human resource selection and orientation (4) manpower training and development (5) work assessment (6) compensation (7) manpower protection (8) company and employee relationship (9) termination of employment. Based on the result of the research, most of the function already effective, they are human resource planning, manpower training and development, work assessment, compensation management, manpower protection, and termination of employment. While human resource recruitment, human resource selection and orientation, and company & employee relationship are ineffective. Based on the weakness were found on the function, the author gives some recommendations and improvement alternatives to be used by PT. Shaftindo Energi as feedback in future human resource development. Keywords: Management Audit, Effectiveness, Human Resource Function, criteria, causes, effect, recommendation